Green economy in post COVID-19 scenario: Nepalese perspective - Koirala, Madan (Applied Science and Technology Annals, 2020)
COVID-19 might bring a change in socio-economic order, like some socio-economists have started to use the term Before COVID -19 (BC) and After COVID -19 (AC) time period of human history. Postindustrial revolution era of developmental trend of the world is taking a shift, as futurist professionals have started to debate from their perspective. Nepal, though dependent on remittance as major share of GDP, is basically green economy based from ecosystem perspective as it was under harnessed. Since, “cereals couldn’t be grown on the smartboard, neither Artificial Intelligence (AI) chips could be eaten”, a paradigm shift is obvious with minimal option. In a juncture of time, Nepalese migrant workers, a major source of revenue contributors are returning back to the country due to COVID-19. An alternative national policy to live within the country being involved in green economy is the major way, to contribute the productivity. Out of the land use types of Nepal, majority of population still engaged in green based economy will be the best direction to adopt. In addition, Nepal as one of the countries worst hit by the impact of climate change, despite having only 0.06% emission of GHGs out of the global share at 2011 value. The country has adopted low carbon emission economic growth path even before the COVID-19 pandemic outbreak.